2013
DOI: 10.1371/journal.pone.0078653
|View full text |Cite
|
Sign up to set email alerts
|

Lactose Intolerance: Lack of Evidence for Short Stature or Vitamin D Deficiency in Prepubertal Children

Abstract: BackgroundThe health consequences of lactose intolerance (LI) are unclear.AimsTo investigate the effects of LI on stature and vitamin D status.HypothesesLI subjects will have similar heights and vitamin D status as controls.Subjects and MethodsPrepubertal children of ages 3-12 years with LI (n=38, age 8.61 ± 3.08y, male/female 19/19) were compared to healthy, age- and gender-matched controls (n=49, age 7.95±2.64, male/female 28/21). Inclusion criteria: prepubertal status (boys: testicular volume <3cc; girls: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…This is particularly striking as BMI SDS was similar for both the IBS subjects and controls, thus excluding the diminutive effect of BMI on 25(OH)D concentration as the reason for the lower vitamin D concentration in IBS. The lack of a diminutive effect of increasing BMI on serum 25(OH)D in patients with IBS is interesting as this phenomenon has been described only in children and adolescents with inflammatory bowel disease[ 6 ], but not in pediatric patients with lactose intolerance[ 15 ] or in healthy subjects[ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly striking as BMI SDS was similar for both the IBS subjects and controls, thus excluding the diminutive effect of BMI on 25(OH)D concentration as the reason for the lower vitamin D concentration in IBS. The lack of a diminutive effect of increasing BMI on serum 25(OH)D in patients with IBS is interesting as this phenomenon has been described only in children and adolescents with inflammatory bowel disease[ 6 ], but not in pediatric patients with lactose intolerance[ 15 ] or in healthy subjects[ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that increased adiposity is associated with vitamin D deficiency [26], [27]. The mechanism of this association is unclear, however, proposed causative factors include poor nutrition, inadequate exposure to sunlight, and the sequestration of vitamin D in fat stores in overweight/obese individuals [28].…”
Section: Discussionmentioning
confidence: 91%
“…According to Alharbi and El-Sohema [ 43 ], individuals with the CC genotype were shorter than those with the TT genotype; presumably, as confirmed by numerous studies, this determined lower milk consumption [ 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 93%